Generative AI for developing personalized male image strategies in barber education - Nersisian, Sevan (Педагогічна Академія: наукові записки, 2026)
The integration of generative artificial intelligence into barbersʼ professional training offers opportunities to systematically develop personalized strategies for menʼs image. The use of generative models enables future masters to learn to analyze individual appearance parameters, current stylistic trends, and client preferences, thereby enabling the adaptation of training programs to the specifics of professional activity. The purpose of the study is to develop a methodological approach to the use of generative artificial intelligence to formulate personalized strategies for menʼs image in the barber training educational process. The study used methods of analyzing scientific sources, modeling male style options with generative neural networks, experimental testing of the developed strategies, and administering questionnaires to participants in the educational process. Results. It is shown that the use of machine learning algorithms enables structuring appearance parameters, stylistic preferences, and professional requirements, thereby enabling accurate prediction of optimal image options and effective planning of educational activities. The study found that the use of generative artificial intelligence increases the efficiency of the educational process, enables the formation of personalized educational trajectories, and promotes the development of critical and creative thinking among students in the field of menʼs style. The use of digital tools not only supports practical skills but also stimulates a deep understanding of modern trends in professional barbering. Сonclusions. Generative artificial intelligence is an effective means of personalizing educational strategies in barber training, thereby contributing to the comprehensive development of professional competencies and opening up prospects for the introduction of innovative technologies into professional education. The practical significance lies in the possibility of applying the developed models in educational institutions and professional salons to optimize curricula and improve the quality of service provision.